2015
DOI: 10.1039/c5cp02406d
|View full text |Cite
|
Sign up to set email alerts
|

Cold water cleaning of brain proteins, biofilm and bone – harnessing an ultrasonically activated stream

Abstract: In the absence of sufficient cleaning of medical instruments, contamination and infection can result in serious consequences for the health sector and remains a significant unmet challenge. In this paper we describe a novel cleaning system reliant on cavitation action created in a free flowing fluid stream where ultrasonic transmission to a surface, through the stream, is achieved using careful design and control of the device architecture, sound field and the materials employed. Cleaning was achieved with pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 37 publications
(39 reference statements)
0
29
0
Order By: Relevance
“…Another potential application to treat biofilm infections harnessing sound is an ultrasonically activated stream. Birkin et al (2015) reported that by applying low-amplitude ultrasound (135 kHz, 120À250 kPa) through a liquid stream directed at a surface, endogenous cavitation nuclei can be sufficiently activated at the solid/liquid interface to disrupt biofilm.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Another potential application to treat biofilm infections harnessing sound is an ultrasonically activated stream. Birkin et al (2015) reported that by applying low-amplitude ultrasound (135 kHz, 120À250 kPa) through a liquid stream directed at a surface, endogenous cavitation nuclei can be sufficiently activated at the solid/liquid interface to disrupt biofilm.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…• the cleaning of brain tissue and prions from surgical steel, the removal of contaminating material from bone transplants [33];…”
Section: Introductionmentioning
confidence: 99%
“…This would then have the potential to either prevent or limit biofilm development, in addition to dispersing and treating any adherent cells already present in the wound bed. The transmission of US via a fluid stream to biotic and abiotic surfaces for the purpose of biological decontamination has recently demonstrated that clinical translation and utility in this field are achievable (Birkin et al ., , ). In order to achieve fundamental change in healthcare practices such as the treatment of chronic wounds, we believe this review exemplifies the need for collaborative and interdisciplinary research to potentiate existing therapies and develop novel treatment modalities.…”
Section: Multifunctional Agents For the Delivery Of Nitric Oxide To Bmentioning
confidence: 99%